2009
DOI: 10.1080/10253890802228178
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and the appraisal-coping process in response to relationship conflicts: Implications for depressive symptoms

Abstract: The present investigation assessed the mediating role of appraisal-coping processes in the relation between forgiveness and depressive symptoms associated with intimate relationship conflicts. Study 1 assessed the role of forgiveness in the context of a severe relationship stressor, namely women experiencing dating abuse, along with the appraisal-coping responses and depressive symptoms associated with such a stressor. Study 2 evaluated the function served by forgiveness among men and women in response to non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 75 publications
(109 reference statements)
5
22
0
Order By: Relevance
“…Thus, primary appraisal shapes the emotional response an individual has to an event, whereas secondary appraisal shapes the behavioral response to the event (Lazarus & Folkman, 1984;Wright & Fitzgerald, 2007). Outcomes associated with a stressful encounter depend on both how it is appraised and the subsequent coping response (Peacock & Wong, 1990;Ysseldyk, Matheson, & Ansiman, 2009). Because events that are appraised more negatively during the primary appraisal process are more likely to tax or exceed an individual's available psychological and material resources, primary appraisal responses, specifically emotional responses, were of interest in the present study.…”
Section: Sexual Harassment Appraisalsmentioning
confidence: 99%
“…Thus, primary appraisal shapes the emotional response an individual has to an event, whereas secondary appraisal shapes the behavioral response to the event (Lazarus & Folkman, 1984;Wright & Fitzgerald, 2007). Outcomes associated with a stressful encounter depend on both how it is appraised and the subsequent coping response (Peacock & Wong, 1990;Ysseldyk, Matheson, & Ansiman, 2009). Because events that are appraised more negatively during the primary appraisal process are more likely to tax or exceed an individual's available psychological and material resources, primary appraisal responses, specifically emotional responses, were of interest in the present study.…”
Section: Sexual Harassment Appraisalsmentioning
confidence: 99%
“…Although the findings of the current study support the concept in the literature of forgiveness creating another chance for the relationship (Tsang & Stanford, 2007;Ysseldyk et al, 2009), the young women also described how forgiving their partners provided them with power and control over the situation because the young women gave their relationship another beginning; they did not identify forgiving their partners as reflecting their lack of power and control over IPV. Similar to the women in Tsang and Stanford's (2007) Communication with partners.…”
Section: Coping To Lessen the Influence And Power Oflpvsupporting
confidence: 48%
“…ysseldyk, Matheson, and Anisman (2009) compared 85 women who were currently experiencing physical or emotional abuse in their relationships to 99 men and women who were not in abusive relationships or had recently experienced a breakup. they found that women experiencing relationship abuse had lower levels of forgiveness and higher levels of depression.…”
Section: Forgiveness and Health In The Rehabilitation Populationmentioning
confidence: 99%